BIM deletion polymorphisms in hispanic patients with non-small cell lung cancer carriers of EGFR mutations (2016)
Background: Germline alterations in the proapoptotic protein Bcl-2-like 11 (BIM) can have a crucial role in diverse tumors. To determine the clinical utility of detecting BIM deletion polymorphisms (par4226 bp/ par363 bp) in EGFR positive non-small-cell lung cancer (NSCLC) we examined the outcomes of patients with and without BIM alterations. Results: BIM deletion was present in 14 patients (15.7%). There were no significant differences between patients with and without BIM-del in clinical characteristics or EGFR mutation type; however, those with BIM-del had a worse overall response rate (ORR) to erlotinib (42.9% vs. 73.3% in patients without BIM-del; p=0.024) as well as a significantly shorter progression-free survival (PFS) (10.8 BIM-del+ vs. 21.7 months for patients without BIM-del; p=0.029) and overall survival (OS) (15.5 BIM-del+ vs. 34.0 months for patients without BIM-del; p=0.035). Multivariate Cox regression analysis showed that BIM-del+ was an independent indicator of shorter PFS (HR 3.0; 95%CI 1.2-7.6; p=0.01) and OS (HR 3.4; 95%CI 1.4-8.3; p=0.006). Methods: We studied 89 NSCLC Hispanic patients with EGFR mutation who were treated with erlotinib between January 2009 and November 2014. BIM deletion polymorphisms (BIM-del) was analyzed by PCR in formalin-fixed paraffin-embedded (FFPE) tissues of tumor biopsies. We retrospectively analyzed clinical characteristics, response rate, toxicity, and outcomes among patients with and without BIM-del. Conclusions: The incidence of BIM-del found in Hispanic patients is similar to that previously described in Asia. This alteration is associated with a poor clinical response to erlotinib and represents an independent prognostic factor for patients who had NSCLC with an EGFR mutation.